2019
DOI: 10.1504/ijcg.2019.098039
|View full text |Cite
|
Sign up to set email alerts
|

Does corporate governance influence the working capital management of firms: evidence from India

Abstract: The study explores the impact of corporate governance on the working capital management of Indian firms. The investigation has been performed using balanced panel data procedures for a sample of 323 Indian non-financial firms listed in the Bombay Stock Exchange for the period 2007-2017. Findings of our study indicate that the CEO duality, one of the nine board indicators play a role in improving the working capital management of the sample firms. The default tax payment of the legal indicator and the additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Al-Mudhaki and Joshi ( 2004) concluded there is a lack of audit committee independence in their representation and composition. Prasad et al (2019) found that CEOs directors who belong to controlling shareholders got higher pay as compared to professional CEOs. Chauhan and Kumar (2017) pointed out that female directors face more attendance problems compared to male directors, and are less likely to be employed in monitoring-related committees.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Al-Mudhaki and Joshi ( 2004) concluded there is a lack of audit committee independence in their representation and composition. Prasad et al (2019) found that CEOs directors who belong to controlling shareholders got higher pay as compared to professional CEOs. Chauhan and Kumar (2017) pointed out that female directors face more attendance problems compared to male directors, and are less likely to be employed in monitoring-related committees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another context, several studies explored corporate governance practices (e.g., Abraham et al, 2015;Al-Mudhaki & Joshi, 2004;Bose, 2009;Chatterjee, 2011;Haldar et al, 2018;Islam, 2016;Katarachia et al, 2018;Kiranmai & Mishra, 2019;Kota & Tomar, 2010;Mayur & Saravanan, 2017;Prasad et al, 2019;Sarkar et al, 2012;Srivastava et al, 2018;Subramanian, 2017;Subramanian & Reddy, 2012). Abraham et al (2015) stated that Indian companies have a high level of compliance with corporate governance disclosure requirements especially, after amendments to Clause 49 as the penalties for noncompliance increase in severity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal values are relevant to holding company management since they can influence human behavior and cause obstructions in the administration of this type of organization's decision-making process. Parada and Vilad as (2010) and Prasad et al (2019) argue that values are the most important aspects of a person's identity, and they determine whether a multinational holding company succeeds or fails. This study uses the personal-value perspective, which is the most popular in social psychology research.…”
Section: Personal Valuesmentioning
confidence: 99%
“…According to Lazaridis and Tryfonidis (2006), ineffective WCM is a major cause of business and start-up failures. Working capital management is a critical part of performance management that could be enhanced (Prasad et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%